Cost-effectiveness of sensor-augmented insulin pump therapy vs continuous subcutaneous insulin infusion in patients with type 1 diabetes in the Netherlands - Roze S; Smith-Palmer J; de Portu S; Dalbaere A; de Brouwer B; de Valk HW (Dove Medical Press, 2019)
Stephané Roze,1 Jayne Smith-Palmer,2 Simona de Portu,3 Alexis Delbaere,3 Bonnie de Brouwer,4 Harold W de Valk5 1HEVA HEOR, Lyon, France; 2Ossian Health Economics and Communications, Basel, Switzerland; 3Medtronic International Trading Sàrl, Tolochenaz, Switzerland; 4Medtronic Trading NL, Heerlen, the Netherlands; 5Leiden University Medical Center, Leiden, the Netherlands Aim: The aim of this study was to perform a cost-effectiveness analysis to establish the cost-effectiveness of sensor-augmented pump therapy (SAP) with automated insulin suspension vs continuous subcutaneous insulin infusion (CSII) alone in patients with type 1 diabetes in the Netherlands.Patients and methods: The analysis was performed using the IQVIA CORE Diabetes Model (CDM) in two different patient cohorts: one with suboptimal glycemic control at baseline (mean age 27 years, mean baseline HbA1c 8.0% [64 mmol/mol]) and the other at increased risk of hypoglycemic events (mean age 18.6 years, mean baseline HbA1c 7.5% [58 mmol/mol]). Clinical input data were sourced from published literature, and the analysis was performed from the societal perspective.Results: In patients with suboptimal baseline glycemic control, SAP improved quality-adjusted life expectancy by 1.77 quality-adjusted life years (QALYs) vs CSII (15.54 QALYs vs 13.77 QALYs) with higher lifetime costs (EUR 189,855 vs EUR 150,366), resulting in an incremental cost-effectiveness ratio (ICER) of EUR 22,325 per QALY gained. In this cohort, sensitivity analyses showed that the influence of SAP on fear of hypoglycemia (FoH) and baseline HbA1c were key drivers of results. In patients at increased risk of hypoglycemia, the gain in quality-adjusted life expectancy with SAP vs CSII was 2.16 QALYs (16.70 QALYs vs 14.53 QALYs) with higher lifetime costs (EUR 204,013 vs EUR 171,032) leading to an ICER of EUR 15,243 per QALY gained. In this patient group, findings were most sensitive to changes in assumptions relating to the incidence of severe hypoglycemic events in the CSII arm.Conclusion: For type 1 diabetes patients in the Netherlands who do not achieve target HbA1c levels or who experience frequent severe hypoglycemic events on CSII, switching to SAP is likely to be cost-effective. Keywords: cost, cost-effectiveness, type 1 diabetes, the Netherlands, sensor-augmented insulin pump therapy